Pengaruh Ekuitas Merek Terhadap Keputusan Pembelian Handphone Android(Studi Kasus Pengguna Handphone Android di Wonogiri) - Nugroho, Hari, Drs. Ma'ruf, MM (2016)
ABSTRACT EFFECT OF BRAND EQUITY PURCHASE DECISION ON ANDROID PHONE (Case Study in Wonogiri Android Mobile Users ) Interest in the study were: 1) to analyze the influence of brand awareness on purchasing decisions Android phones, 2) to analyze the influence of perceived quality on purchasing decisions Android phones, 3) to analyze the influence of brand associations on purchasing decisions Android phones, 4) to analyze the effect of brand loyalty to the purchasing decision of Android phones, 5) to analyze the influence of brand equity on purchasing decisions Android phone. This research is a quantitative research with survey approach. The population is all android based mobile phone users in Wonogiri, samples were taken of 100 people with accidental sampling technique. Data analysis methods: (1) Test the research instrument, namely the validity and reliability, (2) Test the classic assumption, namely normality test, multicollinearity, heteroscedasticity, autocorrelation, (3) Test the hypothesis: multiple linear regression tests, simultaneous analysis ( test F), a partial analysis (t test) and test the coefficient of determination (R2). Based on the result: 1) Brand awareness positive and significant effect on purchasing decisions Android phones, 2) Association brand positive and significant effect on purchasing decisions Android phones, 3) Perception of the quality of positive and significant effect on purchasing decisions Android phones, 4) Loyalty brand positive and significant impact on purchasing decisions Android phones, 5) Brand Equity significant effect together against the Android mobile phone purchasing decisions in Wonogiri, 6) Awareness of the brand is the most dominant variable influencing purchasing decisions Android phone in Wonogiri. Keywords: brand equity, purchase decision, loyalty brand, awaeness brand